SKRINING FITOKIMIA DAN PENETAPAN KANDUNGAN FLAVONOID TOTAL EKSTRAK METANOLIK HERBA BOROCO (Celosia argentea L.) - Abd. Malik; Ferawati Edward; Risda Waris (Faculty of Pharmacy, Universitas Muslim Indonesia, 2014)
Phytochemical Screening and Determination of Total Flavonoids Content of Methanolic Extracts of Boroco Herbs (Celocia argentea L). Boroco plant is often used as a traditional medicine for anti inflammatory, diuretic, hypertension, dysentery. Chemical constituents in boroco herbs (Celocia argentea L.) are alkaloids and flavanoids, glycosides, tannin and saponin (2003) . Each sample extraction using 96 % methanol of maceration method. Then performed to determine the class of phytochemical screening of active compounds are contained in the sample. Determination of total flavanoids done by chang et al method (2002) of Boroco herbs. Result of the study showed the total flavanoids content of methanolic extract of boroco herbs calculated as a rutin for 2.57%.